SMOKING PREVALENCE AND THE IMPACT ON RESPIRATORY FUNCTION AMONG MEDICAL STUDENTS - Островська, К. М.; Долішній, А. М.; Варунків, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The problem of smoking is currently actual for 1.2 billion people around the world, and about 6 million people die every year from smoking-related illnesses. The problem of the smoking prevalence at a young age is devoted to many scientific works. Unfortunately, for the first time in recent years, the prevalence of smoking among adolescents aged 14-17 has increased in Ukraine. That is why the purpose of the study was to assess the prevalence of smoking among students of the first year of the medical faculty of the IFNMU. 74 undergraduate students were examined through anony-mous questionnaires. For the purpose of studying the function of external respiration, peak flowmetry was performed. According to the study, it was found that 40.6% of male smokers and 7.1% of female were smokers. Moreover, with the increase in age, the percentage of smokers in both groups was increasing. It was also found that the number of male students with a decrease in the parameters of external respiration according to the data of the peak expiratory flow, among smokers is higher by an average of 13.0% than non-smokers. Among non-smoking females, the normal rate, according to peak flow, was found in 40.7% of 17-year-olds and 50.0% of 18-year-olds. The lack of representative data did not allow us to perform a similar analysis among smoking females. After analyzing the data, we came to the conclusion that in the age of 17-18 years (reaching adulthood) the prevalence of smoking among males is 1.52 times higher, and among females – 2.53 times. According to peak expiratory flow, smoking may be one of the factors that negatively affects the pulmonary function.